Exploratory study on the adoption of traffic impact fee in the Philippines - Villareal, Francis F. (2007)
Socio-economic development and increased land use activity generate new travel demands on a constrained transportation system in the Philippines. It is imperative that local governments be assisted in generating resources needed to meet increasing transport demands. The study seeks to answer the question, "To what extent can Traffic Impact Fee (TIF) be adopted by local governments in the Philippines to address the inadequacy of future road capacity arising from new developments?" The TIF requires new developments to pay a proportionate cost of improving road capacity. To answer the research question, this paper reviewed the principles and methodologies of different TIF models, reviewed existing legal and institutional frameworks on local fiscal administration and land use planning, and assessed the technical capability and data availability at the local level. It also applied an improvement-driven TIF model that uses a limited area approach on a residential development project in Cabanatuan City and conducted a Traffic Impact Assessment as an integral part of the TIF model. The case study was intended to understand the opportunities and constraints arising from TIF implementation.